Characterization of the dynamic flow response in microfluidic devices - Elgack, Mohammed Elmahdi (2024)
A Master of Science thesis in Mechanical Engineering by Mohammed Elmahdi Elgack entitled, “Characterization of the dynamic flow response in microfluidic devices”, submitted in May 2024. Thesis advisor is Dr. Mohamed Abdelgawad. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).